Detection some Antimicrobial Resistance Genes in Salmonella sp. Isolated from Chicken Meat - Waad Abbas AL-Lami; Ezat H. Mezal (University of Thi-Qar Journal of Science, 2021)
Salmonellosis is a disease condition caused by a large group of bacteria of the genus Salmonella that can affect human being throughout the world. Fresh and processed poultry have been frequently implicated in cases of human salmonellosis. Furthermore, increased consumption of meat and poultry has increased the potential for exposure to Salmonella enterica. Salmonella is one of the leading causes of food-borne diseases. The present study was designed in order to estimate the prevalence of Salmonella spp. in chicken meat in Nasiriyah city (Iraq) and detection of some antimicrobial resistance gene. The period of specimens collection extended from March 2019 to July 2019. One hundred and twenty five (frozen chiken chest meat) collected from the markets of Nasiriyah city. This study showed that out of (125) studied specimens (16) specimens were Salmonella positive (12.8 %). Salmonella were isolated and identified by using bacterial culturing on buffered peptone water, tetrathionate broth, XLD, S.S.Agar, Nuterinte broth and Nutrient agar and confirming tests by API 20E system as well as molecular diagnosis by using and invA genes for Salmonella, all results of these diagnosis methods referred to all isolates belong to Salmonella spp. Salmonella isolates from chicken have been tested for their antibiotic resistance against (10) different antibiotics using the Kirby-Bauer Dissemination Method. All chicken Salmonella isolates are sensitive to Gentamycin ,while were (87.5%) isolates are resistances to Ciprofloxacin and Nalidixic acid , (56.25%) isolates are resistances to Cefotaxim , (43.75%) isolates are resistances to Norfloxacin and Amoxicillin- clavulanic acid , (18.75%) isolates are resistances to Cefixim , (6.25%) isolates are resistances to Amikacin and Azithromycin. The percentage of multidrug-resistant (62.5%) of chicken Salmonella isolates had multi drug resistance. The isolates were tested for the presence of antibiotic resistance genes using traditional polymerase chain reaction (PCR) to identify and antibiotic resistance genes in Salmonella The genes: (gyrA, parC, qnrA, qnrS and qnrB). This study found in isolates of chicken Salmonella isolates as follows: gyrA gene expose in 15/16 isolates (93.75%), parC gene expose in 15/16 isolates (93.75%), qnrB gene expose in 1/16 isolates (6.25%).